Conditioning to optimize technique (Part 1) - Havriluk, R. (Swimming World Magazine, 2019)
Swim training typically emphasizes conditioning. However, emphasizing technique is essential for maximum performance. This two-part series presents options for optimizing technique without compromising conditioning. There are three types of sets that integrate into a conditioning program and provide opportunities to emphasize technique: skill sets, transition sets and test sets. To achieve the maximum benefit from all three sets, a swimmer must be able to accurately gauge stroke rate. This will, in turn, help a swimmer learn to control technique at race pace.